Women´s experiences with being exposed to external aortic compression in the management of postpartum hemorrhage: a qualitative study in Norway - Grethe Heitmann; Karin Meland; Katariina Laine; Eva Marie Flaathen; Ann-Chatrin Linqvist Leonardsen (BMC Pregnancy and Childbirth)
Abstract Background The prevalence and severity of postpartum hemorrhage (PPH) in high-income countries are increasing. Treatment of PPH may, beside causal treatment and volume replacement, include temporizing measures like external aortic compression (EAC). The primary objective of this study was to explore women´s experiences with being exposed to EAC in the management of PPH after vaginal delivery. Methods Ten women were recruited to semi-structured interviews. Reflexive thematic analysis was used to analyze the interviews. Results Three major themes were identified, namely (1) One of many interventions, (2) Need for adjusted information and (3) In safe hands. The participants described that EAC was performed at the same time as other interventions and was, as other interventions, associated with pain. They also described the need for information adjusted to individual needs, prior to application of EAC, while the maneuver was performed, and afterwards. Finally, the participants described feeling safe while EAC was performed. Conclusions Early application of EAC was well tolerated among the majority of the participants. Our findings underline the importance of information about the maneuver and that the information needs to be adjusted to individual needs. Trial registration Not registered.